The Teacher's Guide to Gifted and Talented Education : Practical Strategies for the Classroom - Lafferty, Kate (Routledge, 2024)
"The Teacher's Guide to Gifted and Talented Education: Practical strategies for the Classroom is a guide on ways to build and enhance your understanding of gifted learners with evidence-based hands-on strategies to use in the classroom. Whether you are looking to improve your own practice or starting out as a Gifted Education coordinator in your school, this book will guide you through each step. Informed by research, and covering essential topics from theoretical frameworks to differentiation and innovative pedagogies, each chapter includes a 'Back to basics' section, which provides the key information for those wanting just enough to get going, a 'Taking it further' section, which offers a more in-depth critique of the content and a 'Chapter reflection' which provides an opportunity to plan and set goals. Filled with tips, strategies, checklists and templates, and written by an author with extensive practical and research experience in the field, this book is an essential resource for all educators, from early childhood through to secondary"--